Pembuatan Sistem Informasi Akuntansi dan Inventory Control untuk UD. 88 - Wijoyo, Hendra Wennady; Setiawan, Alexander; Setiabudi, Andy (Jurnal Infra, 2015)
On this current situation, UD. 88 is not using transaction recording system with good information flow. All transaction recording still done in manual way, it makes UD. 88 very susceptible to exposure and loss caused by overstock and stockout costs.Based on this background, we designed a structural accounting information system with inventory control that can overcome the problems. That system was build using Microsoft Visual Studio 2010 and MySQL as database.The result obtained from the system are master recording, purchase and sale transaction recording, inventory control, stock report, purchase report, sales report, general ledger, and financial statement such as income statement and balance sheet.